Foreign direct investment attraction in the Baltic States - Svetlana Saksonova (Business: Theory and Practice, 2014)
This paper considers the importance of macroeconomic factors as well as investment climate for foreign direct invest ment attraction in the Baltic states. It reviews some of the indicators for measuring the investment climate and their usefulness as indicators of strength of FDI attraction and uses the results of econometric analysis to consider relative importance of various macroeconomic factors. The results suggest that perceptions of corruption and fiscal policy are some of the more important drivers of FDI attraction. The paper also considers several measures that could improve foreign direct investment attraction in the Baltic States such as expanding the protection of property rights and improving the quality of infrastructure.